Generalizations for Certain Bazilevic Functions - YAVUZ, EMEL; DAYMAZ, TUĞBA; Owa, Shigeyoshi (SEAMS - Southeast Asian Mathematical Society, 2021)
For analytic functions f(z) in the open unit disk U, an interesting class A(alpha, beta, gamma) is considered. The object of the present paper is to discuss some properties for f(z) in the class A(alpha, beta, gamma) and the class A(alpha, beta, infinity) for gamma -> infinity.
Keywords: Bazilevi´c Function; Starlike Function; Close-to-convex Function; Coefficient Inequality